Community Participation and Organizational Commitment in the Implementation of the Biofloc-Based Food Security Program in Tanjung Harapan Village - Husna, Nur Aprilia; Akmal, Artha Dini (Department of Government Studies, Universitas Syiah Kuala, 2025)
This study aims to analyze the participation and commitment of program implementers in the Bioflok program within the context of a food security initiative in Tanjung Harapan Village. The focus of the research is on neighborhood heads (RT) and youth organizations (Karang Taruna) as local-level actors. The study employs a descriptive qualitative approach using in-depth interviews with key informants, including RT leaders, members of Karang Taruna, village officials, and BPD members. The findings reveal that participation in decision-making was minimal, characterized by a top-down approach with no deliberative process. During the implementation and benefit utilization stages, participation varied greatly; some RTs demonstrated collective involvement and local initiative, while others operated individually with limited engagement. The level of commitment also varied: successful RTs showed strong affective, continuance, and normative commitment, whereas unsuccessful ones tended to be involved only administratively, lacking emotional attachment or long-term responsibility. This study concludes that the success of the Bioflok program does not solely depend on participation, but also on the extent to which implementers possess a sense of ownership, personal responsibility, and social structures that support program sustainability.